Midiatização do conflito Rússia-Ucrânia em capas de jornais do Brasil e Suécia: discursividades de guerra em curso - Hartmann, Camila (2024)
This thesis takes an investigative approach that seeks to answer the research problem of how the newspaper front pages from Brazil and Sweden manage the production of meanings about the mediatized war between Russia and Ukraine. By reflecting on the developments in news coverage in Sweden and Brazil, we aim to reveal how the conflict is discursively framed from these two distinct and distant realities. This comparative analysis highlights the similarities and differences between the front pages from Brazil and Sweden. Representing the mainstream media in their respective countries, we analyze how the newspapers Folha de S.Paulo (Brazil) and Dagens Nyheter (Sweden) frame discursivities about the war in accordance with their production contexts. We sought to reveal the meanings produced about the Russian-Ukrainian conflict in the front pages' discursivity. Furthermore, we investigated the mediatization of the war discoursivities in progress in Folha de S.Paulo and Dagens Nyheter and identified the newsworthiness pattern constructed about the war by the Brazilian media and the Swedish media. From the proposition that circulation is also production, in the empirical work of this thesis we challenge ourselves to reflect on the innovative processes in production that affect and are affected by circulation. We therefore propose to think more about the production pole as a reference for studying circulation. Our tentative effort consisted of an analytical arrangement that conceived the production of newspapers as textualized productions, discursively materialized on the front pages, and updated in mediatized circulation. The corpus of this study consists of printed front pages published by these newspapers during the first year of the conflict, spanning February 24, 2022, to February 24, 2023. Specifically, the analytical corpus comprises 69 front pages. To conduct the analysis, we employed a methodological framework based on discursive semiotics, aiming to uncover the intersections between social and discursive processes. Our analytical development reveals the peculiarities of productive poles whose institutional legitimacy is constantly put to the test in the process of circulation. They update themselves (or so they try) in the face of new emerging possibilities in conjunction with the reception. The coverage by Folha de S.Paulo frames the conflict from an external perspective, while Dagens Nyheter employs an approach that is more proximate and familiar to its context. This divergence reflects the differing news values that shape the journalistic production of a Brazilian and a Swedish newspaper in relation to the conflict. The newsworthiness criteria vary, suggesting that a distinct perception or grammar of conflict is at play in Brazil – one not necessarily defined by conventional warfare, but by conflict dynamics heavily influenced by political polarization and the proliferation of disinformation bubbles on digital platforms. While Europe and much of the world are horrified by Putin’s brutality, Brazil exists in a state of intermittent conflict.